Класифікація країн європейського союзу за основними соціально-економічними показниками методом головних компонент - Гибкіна, Н. В.; Сидоров, М. В.; Стороженко, О. В. (ХНУРЕ, 2017)
The classification problem of the European Union countries on the essential economic and social indicators in 1994-2016 is considered. To sorting the EU member into groups, it was suggested to use the method of main components based on 22 socio-economic indicators for each country. The obtained results graphically display the position of the countries on the plane of the first two main components.
Keywords: метод головних компонент; економічне моделювання